Prevalence of insulin induced lipodystrophy in patients with diabetes mellitus in a tertiary care centre: a cross sectional study - Bezawada, Shravani; V., Anuradha H.; Kalra, Pramila (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Diabetes Mellitus is a spectrum of common metabolic disorders whose management mainly lies in treating the patients with oral hypoglycaemic drugs and insulin along with the dietary and lifestyle modifications. Lipodystrophy is the most neglected adverse drug effect caused by injecting insulin. The main objective of this study was to assess the prevalence of lipodystrophy at the insulin injection sites in patients suffering from diabetes mellitus (Type 1 and Type 2). Methods: A cross-sectional study was conducted in the Department of Endocrinology on 250 diabetic patients taking insulin injections based on inclusion and exclusion criteria. The demographic features and anthropometric measurements were noted. Insulin injection sites were examined clinically by inspection and palpation for presence of swelling like lipodystrophy, injection marks and signs of allergy like erythema etc. Lipodystrophy was graded from 0-3 and denoted as lipohypertrophy or lipoatrophy. The results were tabulated and presented accordingly. Results: In this study, out of 250 patients 17 (6.8%) patients presented with insulin induced lipodystrophy. Lipohypertrophy was the most common presentation and only one case presented with lipoatrophy. Conclusions: It can be concluded from the present study that lipodystrophy which is an important adverse effect due to insulin injection needs to be monitored regularly in every patient taking insulin for better control of glucose levels.